Belize. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Belize during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as rural development, agrotourism, technologies, irrigation, drainage, public policies, food security, economic development, agriculture. organic and postharvest handling. Finally, technical assistance was provided to improve the value chains of tilapia, corn, beans, and sugar cane.